Certain Investigation Of Real Time Networked Control Dc Motor Using Smith Predictor - et.al, Dharshan Y (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, DC motor is controlled by direct structure Networked Control System (NCS) with smith predictor control strategy. Mathematical model of DC motor is identified by empirical model building and estimated Round Trip Time Delay (RTT) is considered as time delay which is induced by network. Delay time which is induced in Networked DC motor is compensated with the smith predictor controller then the designed controller algorithm is comparatively analyzed with conventional PI controller. The simulation results are formulated for identified motor model with real time network. In addition to that the hardware fabrication of real time Networked DC motor has been developed and the results of both the simulation and hardware implementation are compared.